Enhancing Student Skills through Family Medicinal Plants: A Community Service Initiative - Faizatul Widat; Widiyawati Widiyawati; Siti Maysaroh Agustin; Syaviatur Rosi; Latifatun Nisa (Al-Qalam Institute, 2023)
This research focuses on the implementation of reforestation using Family Medicinal Plants (TOGA) as a reforestation solution, which has barren land. This research addresses serious problems related to dry land in the MI Azzainiyah II environment. This research uses a field research approach and uses qualitative descriptive methods. Data collection was conducted through interviews, participant observation, and documentation. The validity of the data is ensured through triangulation of data sources, which involves using multiple sources to obtain information, and triangulation of methods by comparing data from interviews, observations, and documentation. Data is analyzed through several stages, including data reduction, data display, and verification to conclusions. This research shows the positive impact of Family Medicinal Plants (TOGA) training on the knowledge and skills of MI Azzainiyah II students in caring for the school environment. The data collected shows a significant increase in students' understanding of TOGA after attending the training. This research aims to increase students' understanding and practical skills in TOGA farming, which can be applied directly in their surrounding environment.